2002
DOI: 10.1088/0022-3727/35/13/316
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear strain and DC bias induced piezoelectric behaviour of electrostrictive lead magnesium niobate-lead titanate ceramics under high electric fields

Abstract: Laser Doppler interferometry has been used to determine the strain and piezoelectric response of Pb(Mg1/3Nb2/3)O3-PbTiO3 (PMN-PT) electrostrictive ceramics as a function of electric fields up to 4 MV m-1, frequencies between 0.1 Hz and 2.5 kHz and DC bias fields up to 3 MV m-1. The strain and polarization of PMN-15 with a composition of 0.9PMN-0.1PT and PMN-38 with a composition of 0.85PMN-0.15PT both produced by TRS ceramics, have been measured at room temperature. The strain and polarization responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…12,13 Figure 1 shows some measured Q 33 values from literature for single crystal, ceramic, and thin film samples from the PMN-PT series. [12][13][14][15][16][17][18][19][20][21][22] Most quoted values fall between 1 and 3ϫ10 Ϫ2 C Ϫ2 m 4 and, though there is often no apparent compositional trend, some studies have shown a rise in Q 33 with PT content. 15 In the absence of an external bias, relaxors are centrosymmetric and therefore do not display the piezoelectric effect.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Figure 1 shows some measured Q 33 values from literature for single crystal, ceramic, and thin film samples from the PMN-PT series. [12][13][14][15][16][17][18][19][20][21][22] Most quoted values fall between 1 and 3ϫ10 Ϫ2 C Ϫ2 m 4 and, though there is often no apparent compositional trend, some studies have shown a rise in Q 33 with PT content. 15 In the absence of an external bias, relaxors are centrosymmetric and therefore do not display the piezoelectric effect.…”
Section: Introductionmentioning
confidence: 99%
“…A transverse strain measurement system has been developed based on a ZYGO laser Doppler interferometer (ZMI 2000, ZYGO Corp.) [4]. We have used this system to investigate electroactive polymer actuators fabricated from silicone (Dow Corning HSIII RTV) films.…”
Section: Methodsmentioning
confidence: 99%
“…The system uses a heterodyne detection technique and features a wide bandwidth, high stability, easy optical alignment and the ability to measure a wide range of displacement and frequency [4]. The static and dynamic strains of the actuators have been measured as functions of amplitude and frequency of applied electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…As another typical electrostrictive material, electrostrictive ceramics have higher dielectric permittivity than electrostrictive polymers and piezoelectric ceramics that is beneficial to reducing the output impedance of the device. They have higher electrostrictive coefficient than electrostrictive polymers and even have higher effective piezoelectric coefficients than piezoelectric ceramics 18, which is beneficial to the ability of energy conversion for harvesters. However, energy‐harvesting research based on electrostrictive ceramics has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%